(untitled) (Research, Society and Development, 2022)
The need to change from the traditional teaching model to the virtual one due to the social isolation leads to discussions about maximizing the use of Information and Communication Technologies (ICT) in education. This study aimed to evaluate the profile of the use of technologies in education and the acceptance and resistance to the use of ICT by faculty members in higher education in health during the COVID-19 pandemic. This study is a quantitative observational cross-sectional study, carried out from March to December 2020, with the universe of investigation being all the teachers linked to the undergraduate level courses in the health area of a higher education institution. The results show that of all the professionals surveyed (n = 248), 46.4% (n = 115) had already had access to knowledge or some training in ICT. When comparing data from before and during the pandemic, we observed a significant increase in the indicators of teachers’ experience in remote classes (from 5.2% to 72.2%), knowledge about virtual learning resources (from 8,1% to 60.9%), consideration of the importance of knowledge about ICT (from 46.4% to 98.4%) and training in the area (from 19.4% to 55.7%), besides the reduction in the level of difficulty of teachers regarding the change from the traditional model to the technological one (from 26.6% to 3.6%). We conclude that most teachers improved their acceptance of ICT use during the pandemic. The transition from the traditional to the virtual model positively impacted this process.